2022
DOI: 10.2196/33059
|View full text |Cite
|
Sign up to set email alerts
|

Gaming Activity and Possible Changes in Gaming Behavior Among Young People During the COVID-19 Pandemic: Cross-sectional Online Survey Study

Abstract: Background Young people’s daily lives and social interactions changed remarkably during the COVID-19 pandemic as schools and cinemas closed, leisure activities were cancelled, and gatherings were regulated. Questions have been raised by the media, schools, policy makers, and research communities about the effect on young people’s online behaviors. Objective This cross-sectional study aimed to study self-reported changes in gaming, focusing on a younger … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 70 publications
2
19
0
1
Order By: Relevance
“…However, since young adults tend to have the highest rates of screen time and smartphone usage, this group is also the primary population investigated in studies of screen time [75]. Our study is consistent with recent studies related to screen time in terms of sample composition [76,77]. Moreover, to reduce the potential influence of this selection bias, we applied covariance analysis in the model to control the effect of age, gender, and occupation.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…However, since young adults tend to have the highest rates of screen time and smartphone usage, this group is also the primary population investigated in studies of screen time [75]. Our study is consistent with recent studies related to screen time in terms of sample composition [76,77]. Moreover, to reduce the potential influence of this selection bias, we applied covariance analysis in the model to control the effect of age, gender, and occupation.…”
Section: Limitations and Future Directionssupporting
confidence: 83%
“…88 The 11 studies conducted on children and adolescent GD were associated with: age (i.e., being adolescent), 79,82,89 gender (i.e., being male), [82][83][84]86,[89][90][91][92] maladaptive coping regulatory styles, 86 poor social support, 83,86,89 depressive and anxiety symptoms before the COVID-19 pandemic, 76,92 poor mental health, 83 academic stress, 86 unhealthy parental care styles, [81][82][83] addictive gamer profile, 90,91 and excessive use of social networks. 84 With regard to adults, eight studies showed an increased risk of developing GD symptoms in association with age (i.e., being younger than 30 years), 77,79 gender (i.e., being male), 79,87 loneliness, 79,93 maladaptive self-regulation style, 79,88 high impulsivity, 79 depressive and anxiety symptoms before the COVID-19 pandemic, 79 psychological distress, 88,94 low physical activity, 79,94 being unemployed, 94 and being affected by COVID-19. 77 Another two studies reported no significant association between the prevalence of GD and anxiety 85 or being self-isolated or quarantined.…”
Section: Study Outcomesmentioning
confidence: 99%
“…In line with what was observed in previous studies, [122][123][124] in the present systematic review, gender and age differences with regard to GD emerged: potentially problematic gaming symptoms were found to be more likely among males than females 79,87 and among younger gamers. 77,79,82,89 Furthermore, high levels of loneliness and poor social support, 79,83,86,89,93 maladaptive coping regulatory styles, 86,88 and depressive and anxiety symptoms 76,79,83,88,92,94 resulted in risk factors for GD in both young people and adults. Such results support what was reported by previous studies, in which these factors were indicated as risk elements for problematic gaming.…”
Section: Principal Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of online gaming and social media use (SMU) and screen times significantly increased during the lockdown in a representative sample of 1221 adolescents (10–17 years) [32]. Online gaming increased in Indian college students [33] and Malaysian medical students [34], 1501 web panel Swedish participants (25–39 years) and was associated with psychological distress, reduced physical activity, and unemployment [35] in an online international cross-sectional study among adults [1 ▪ ]. IGD increased in the general population, especially younger people in a Japanese study [7 ▪ ].…”
Section: Internet Gaming Disordermentioning
confidence: 99%